Variation in grain yield losses due to fall armyworm infestation among elite open-pollinated maize varieties under different levels of insecticide application - Kenyi, J.J.; Mengesha, W.; Abe, A.; Menkir, A.; Meseka, S. (MDPI, 2024)
Maize is an important food and industrial cereal crop that serves as the main source of energy for millions of low-income people in sub-Saharan Africa (SSA), but its production and productivity are constrained by many constraints, among which the fall armyworm (FAW) is the major one. The use of insecticides is the most effective control measure for the FAW. However, excessive use of chemical insecticides has environmental and health implications, and it can be expensive for resource-poor farmers. The objective of this study was to evaluate the extent of variation in yield losses due to the FAW among some elite maize open-pollinated varieties (OPVs) under two levels of insecticide application and control (0 application). In a two-year field study, 10 elite maize OPVs were evaluated under two levels of emamectin benzoate (5% WDG) applications and the control: 75 and 150 mL of spray solution per 20 L of water. The experimental design was a randomized complete block with three replications. The data were collected on grain yield (GY) and FAW leaf damage rating (LDR). The LDR was conducted on a 1–9 scale and used to categorize the maize varieties as resistant (1–4), moderately resistant (4–6), and susceptible (6–9). Significant varietal differences were obtained for GY and LDRs. The GY of the varieties under control (0 mL), 75 and 150 mL insecticide applications ranged from 3.3 t ha−1 (DTSTR-Y SYN-13) to 4.6 t ha−1 (PVA SYN-3), from 4.5 t ha−1 (DTSTR-Y SYN-13) to 6.4 t ha−1 (PVA SYN-13), and from 4.2 t ha−1 (DTSTR-Y SYN-13) to 6 t ha−1 (DTSTR-Y SYN-14), respectively. No significant differences in GY were found between the application of 75 and 150 mL of insecticide application. The relative loss in GY among the varieties under control (0 mL) differed with an increase in the level of insecticide application. The relative GY loss at the 75 mL insecticide application ranged from 18% (PVA SYN-3) to 38% (DTSTR-Y SYN-15) with a mean of 27%, whereas at the 150 mL insecticide application, it varied from 13% (PVA SYN-3) to 42% (DTSTR-Y SYN-15), with a mean of 26%. All the varieties exhibited moderate resistance to FAW, except DTSTR-Y SYN-14, which was susceptible. The varieties PVA SYN-3 and PVA SYN-13 were the most consistent in GY across the three insecticide treatment levels. The mean performance of the varieties for FAW leaf damage ranged from 4.0 (SAMMAZ-15) to 6.2 (DTSTR-Y SYN-14), from 4.5 (SAMMAZ-15) to 6.3 (PVA SYN-6), from 4.5 (SAMMAZ-15) to 6.3 (DTSTR-Y SYN-14), and from 3.5 (SAMMAZ-15) to 5 (DTSTR-Y SYN-14) for LDR 1, LDR 2, LDR 3, and LDR 4, respectively. The use of moderately resistant varieties, combined with timely spraying of emamectin benzoate at 75 mL provided adequate management for the FAW infestation and sustained high maize grain yield.